Effects of school resource officers on school crime and responses to school crime - Gottfredson, Denise C. (Criminology & public policy, 2020)
Research We examined the effects of an increase in school resource officer (SRO) staffing on schools in a sample of 33 public schools that enhanced SRO staffing through funding from the Department of Justice's Community Oriented Policing Services Hiring Program and a matched sample of 72 schools that did not increase SRO staffing at the same time. In longitudinal analyses of monthly school-level administrative data, we compared the treatment and comparison schools on disciplinary offenses and actions. We found that increased SROs increased the number of drug- and weapon-related offenses and exclusionary disciplinary actions for treatment schools relative to comparison schools. These negative effects were more frequently found for students without special needs. Policy Implications The study findings suggest that increasing SROs does not improve school safety and that by increasing exclusionary responses to school discipline incidents it increases the criminalization of school discipline. We recommend that educational decision-makers seeking to enhance school safety consider the many alternatives to programs that require regular police presence in schools.